PENEGAKAN HUKUM DALAM PUTUSAN HAKIM UNTUK PERKARA YANG MENIMPA MASYARAKAT KECIL - Paramitha Ariana; Yusuf Setyadi (JOURNAL OF LAW AND NATION, 2023)
Along with the development of science and technology from time to time of civilization, humans also experienced changes, and then new problems arose, of course, all of which needed more progressive legal rules to provide balance to these social changes. Nowadays there are often legal cases that refer to "Sharp at the Bottom, Blunt at the Top". To provide a view that often occurs in society, the role of law enforcement is needed to uphold legal certainty and justice, with the intention that the law can apply as fairly as possible to all circles of the Indonesian people.